2011
DOI: 10.1007/s13361-011-0180-2
|View full text |Cite
|
Sign up to set email alerts
|

Direct Quantitative Analysis of a 20 kDa PEGylated Human Calcitonin Gene Peptide Antagonist in Cynomolgus Monkey Serum Using In-Source CID and UPLC-MS/MS

Abstract: PEGylation is a successful strategy to improve the pharmacokinetic and pharmaceutical properties of therapeutic peptides. However, quantitative analysis of PEGylated peptides in biomatrix by LC-MS/MS poses significant analytical challenge due to the polydispersity of the polyethylene glycol (PEG), and the multiple charge states observed for both the peptide and PEG moieties. In this report, a novel LC-MS/MS method for direct quantitative analysis of 20 kDa PEGylated CGRP[Cit, Cit] in cynomolgus monkey serum is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…This technique is called in-source fragmentation-or in-source collisioninduced dissociation. In-source fragmentation has been used in structural elucidation ( 14 ), compound identifi cation (15)(16)(17), compound profi ling ( 18 ), and bioanalysis ( 19 ). In-source fragmentation of HP-␤ -CD, which was promoted by increasing declustering potentials on a 4000QTRAP mass spectrometer, led to glycosidic-bond cleavage and simultaneous fragmentation of all the HP-␤ -CD …”
Section: In-source Fragmentation For the 2d-lc-if-ms/ms Approachmentioning
confidence: 99%
“…This technique is called in-source fragmentation-or in-source collisioninduced dissociation. In-source fragmentation has been used in structural elucidation ( 14 ), compound identifi cation (15)(16)(17), compound profi ling ( 18 ), and bioanalysis ( 19 ). In-source fragmentation of HP-␤ -CD, which was promoted by increasing declustering potentials on a 4000QTRAP mass spectrometer, led to glycosidic-bond cleavage and simultaneous fragmentation of all the HP-␤ -CD …”
Section: In-source Fragmentation For the 2d-lc-if-ms/ms Approachmentioning
confidence: 99%
“…An alternative approach has been developed for the analysis of PEGylated peptides. In this case, IS‐CID was used to release the unconjugated peptide or therapeutic agent moiety that could subsequently be analyzed by MRM of the collision fragments produced in the ESI source . The peptide fragments can be selected and analyzed as surrogates for the PEGylated peptides.…”
Section: Introductionmentioning
confidence: 99%
“…The novel method involves HPLC separation of the PEGylated small molecule, followed by in-source fragmentation in the instrument ionization source, generating a small molecule pegcantratinib-specific fragment ion that can be used as surrogate for the quantitative analysis. Excellent sensitivity was achieved, with an LLOQ below values previously published for PEGylated molecules [ 10 , 11 ]. We have successfully validated the method according to the EMA guidance on bioanalytical method validation [ 12 ] and demonstrated its applicability to determine the drug's tumor distribution in skin tumor punch biopsies obtained from patients with CYLD mutations participating in the current clinical trial.…”
Section: Discussionmentioning
confidence: 69%
“…The mass spectrums generated show broad continuous peaks due to the size and charge distributions of PEG that are difficult to interpret and generally not usable for quantitative analysis [ 9 ]. However, recent papers have demonstrated that PEGylated therapeutic agents undergo collision-induced dissociation in the ionization source (in-source CID) of the mass spectrometer, generating nonPEGylated precursor ions that can be used for drug quantification [ 10 , 11 ].…”
mentioning
confidence: 99%